Global Warming: the North will be as impacted as the South - Frédéric Durand (Territoire en Mouvement)
The media, like many policy makers and researchers, tend to assume that global warming may well have a greater impact on so-called “developing countries” than on those which industrialized first. Yet modeling clearly shows that changes will be more significant at higher latitudes. Additionally, technological sophistication could paradoxically be a source of fragility. It is therefore incorrect to state that the South would be more vulnerable. This position is also problematic because it hinders the decision to reduce greenhouse gas emissions in the North.